LAW ENFORCEMENT AGAINST CRIME SMUGGLING OF USED CLOTHING IMPORTS (STUDY CENTER TANJUNG COURT RULING KARIMUN NUMBER 107 / PID.SUS / 2014 / PN TBK AND CAPE CENTER COURT RULING KARIMUN PID.SUS No. 217/2015 / PN TBK) - Iryanti Sagala; Syafruddin Kalo; Madiasa Ablisar; Chairul Bariah (USU LAW JOURNAL, 2017)
ABSTRACT In this thesis, the author raised the issue of Law Enforcement Against the Crime of Trafficking Used Clothing Imports (Study District Court of Tanjung Balai Karimun No. 107 / Pid.Sus / 2014 / PN Tbk and the District Court's Decision No. 217 Tanjung Balai Karimun Pid.Sus / 2015 / PN Tbk). The theme selection triggered by the smuggling of used clothing was banned by the government, because it hurt the government in terms of revenue in the country, especially the loss of state revenues from customs duties and other charges which should have been received by the Director General of Customs and Excise. There are several options related to the crime of smuggling of used clothing, namely Law No. 17 of 2006 on the Amendment of Act No. 10 of 1995 on Customs, Trade Minister Regulation No. 51 / M-DAG / PER / 7/2015 on Prohibition of Import Used clothing, Trade Minister Regulation No. 54 / M-DAG / PER / 10/2009 on General provisions field of imports, and the Minister of Industry and Trade No. 642 / MPP / Kep / 9/2002 on the amendment Annex I to the Decree of the Minister of Industry and Trade No. 230 / MPP / Kep / 7/1997 on goods set import trade system. The author of this paper uses normative juridical method to approach law (statute approach) and the approach of the case (case approach). By using the above study, the authors obtained the answers to existing problems that the District Court of Tanjung Balai Karimun No. 107 / Pid.Sus / 2014 / PN Tbk and District Court of Tanjung Balai Karimun Pid.Sus No. 217/2015 / PN Tbk same -Same subject to criminal Article 102 (a) of Law No. 17 of 2016, with the sound: every person transporting imported goods that are not listed in Article 7A paragraph (2) had been convicted of smuggling in the field of import by sanctions imprisonment of a minimum of 1 (one ) years imprisonment and a maximum of 10 (ten) years and fined at least Rp. 50.000.000, - (fifty million rupiah) and Rp. 5,000,000,000, - (five billion rupiah). But these two cases different sanctions imposed. The difference of the decision can be caused due to lack of unanimity view of the judges in assessing a case the same or equivalent. In addition the maximum limit and the minimum limit given discretion to judges to convict may also cause differences in punishment. Keywords: Crime of Smuggling, Used Clothing Imports